Communication: basic nursing instrument to look after mother of newborn under phototherapy - Antonia do Carmo Soares Campos; Maria Vera Lúcia Moreira Leitão Cardoso; Lorita Marlena Freitag Pagliuca; Lídia Aparecida Rossi (Rev Rene)
This study aimed to learn about the process of communication between the health team and the mothers of newborns under phototherapy in the light of the Humanistic Theory’s presuppositions. It is characterized as a descriptive, qualitative study guided by the Phenomenological Nursing Process implemented with 25 mothers of newborns under phototherapy, in Fortaleza-CE. The data were collected from January to March 2005, with participant observation and interview in two different moments before and after the implementation of an educational program. Out of the speeches extracted from the fi rst phase, it was possible to identify the theme: communication and the subthemes: damaged communication with the health team; lack of communication of the health team and, in the second phase, the subtheme: reactions of the mother after effective communication with the nurse. It was concluded that the effective communication of the nurse contributed for the well-being of the mothers whose child was under phototherapy.